2021
DOI: 10.1007/s10854-021-05885-8
|View full text |Cite
|
Sign up to set email alerts
|

Optical, thermal and radiation shielding properties of B2O3–NaF–PbO–BaO–La2O3 glasses

Abstract: The techniques of melt-quenching were used to generate 53B2O3 -2NaF -27PbO -(20 − )BaO -La2O3 (0 ≤ ≥ 15) . XRD patterns have established the amorphous character of glass samples. There is clear evidence of the role of La2O3 modifier in the glass network. The thermal characteristics were identified to increase with an increase in La2O3 content. Increasing La2O3 increases the linear and non-linear optical bandgap energy and the Urbach energy. By adding La2O3 to the glass samples, the refractive index, molar pola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The effects of inclusions that modify glass, such as halide ions (ZnF2), as well as structural alterations brought on by BO3/BO4 ratios, were carefully examined [16][17][18][19][20]. ZnO is a well-known material due to its low cost, non-toxicity, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of inclusions that modify glass, such as halide ions (ZnF2), as well as structural alterations brought on by BO3/BO4 ratios, were carefully examined [16][17][18][19][20]. ZnO is a well-known material due to its low cost, non-toxicity, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many benefits of glasses are identified, including their lower manufacturing costs, ease of manufacturing, and the substantial clarity of glasses for visible light have come to prominence. These advantages encouraged researchers to investigate glasses as attractive materials for radiation shielding against gamma-ray, x-ray and neutron radiation shielding [11][12][13][14][15][16][17][18][19][20]. Kebaili et al reported the parameters of γ-ray shielding for ternary lithium borotellurite glasses (TeLiB) using Geant4 code [14].…”
Section: Introductionmentioning
confidence: 99%
“…The results provided scientific information to manufacture new materials for several applications linked to nuclear technologies. M I Sayyed et al investigated many physical features of high-density glasses and estimated their shielding parameters for gamma photons [17].…”
Section: Introductionmentioning
confidence: 99%
“…The structural, optics, and influence of gamma irradiation of the NaF-CaF 2 -B 2 O 3 glass system are investigated by El Batal et al [22]. Abd El-Rehim [23] and Shaaban et al [24] examined the effects of La 2 O 3 on the optical, thermal, and radiation characteristics of NaF -BaO -PbO -B 2 O 3 glasses.…”
Section: Introductionmentioning
confidence: 99%